2018
DOI: 10.1051/parasite/2018058
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the new integrated strategy to control the transmission of Schistosoma japonicum in China: a systematic review and meta-analysis

Abstract: Since 2004, the national schistosomiasis control strategy in China has shifted from the morbidity control strategy (conventional strategy) to an integrated strategy (new strategy). We investigated the effectiveness of the new strategy and compared it against the conventional strategy. We retrieved from electronic databases the literature regarding the new strategy published from 2000 to 2017. The effect of the new or conventional strategy on infection by Schistosoma japonicum of humans and snails (Oncomelania … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…The current national control strategy for the Dongting Lake area and the P.R. China as a whole employs a multi-component integrated approach with mass administration of praziquantel to humans and bovines as its cornerstone - combined with snail control through chemical mollusciciding and environmental modification; improved sanitation through the supply of safe drinking water and latrines; health education aimed at effectively increasing people’s knowledge of schistosomiasis; and removal of cattle, water buffaloes and sheep from all endemic areas ( 4 , 7 , 25 , 63 , 64 ). One area that highlights the effectiveness of this approach is Junshan District, in the Dongting Lake region; Li et al ( 63 ) showed that the multi-component control tactic resulted in a decrease in the prevalence of schistosome infection in residents from 3.44% in 2006 to zero in 2016 after removal of all animals in 2013.…”
Section: Current Strategies and Progress On Schistosomiasis Controlmentioning
confidence: 99%
“…The current national control strategy for the Dongting Lake area and the P.R. China as a whole employs a multi-component integrated approach with mass administration of praziquantel to humans and bovines as its cornerstone - combined with snail control through chemical mollusciciding and environmental modification; improved sanitation through the supply of safe drinking water and latrines; health education aimed at effectively increasing people’s knowledge of schistosomiasis; and removal of cattle, water buffaloes and sheep from all endemic areas ( 4 , 7 , 25 , 63 , 64 ). One area that highlights the effectiveness of this approach is Junshan District, in the Dongting Lake region; Li et al ( 63 ) showed that the multi-component control tactic resulted in a decrease in the prevalence of schistosome infection in residents from 3.44% in 2006 to zero in 2016 after removal of all animals in 2013.…”
Section: Current Strategies and Progress On Schistosomiasis Controlmentioning
confidence: 99%
“…It is also considered as the second most socioeconomically devastating condition after malaria by the World Health organization because of its high prevalence in Africa and the far east causing considerable mortality and morbidity [2,3]. Especially in China, S. japonicum has reached a criterion of elimination, as well as, transmission interruption statuses with greater efforts [4], yet it remains a major health problem in the endemic villages of many provinces connected along Yellow river and Yangtze-Jiang basins [5,6]. Despite the transmission control status, the focal transmission of S. japonicum is still vastly prevalent due to the risk of an epidemic rebound in autonomous regions of Yunnan Province especially like Dali, Lijiang, Chuxiong, and Honge city minorities.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been identified as important to reduce schistosomiasis japonica levels across P.R. China [ 22 , 26 , 27 , 29 , 39 , 42 , 95 97 ]. The value of integrated One Health approaches has been described in the context of Schistosoma mekongi elimination efforts in Lao PDR and Cambodia [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Solid evidence demonstrates that sustainable control and particularly interruption of transmission and elimination of human schistosomiasis is only possible through multipronged long-term strategies that are adapted to local conditions, sustained by political commitment and funded adequately [ 22 , 27 , 63 , 74 , 92 ]. Intervention strategies need to be based on (predictive) risk mapping and combine different interventions that are tailored to the local socio-economic and epidemiological context through close consultation with the local population.…”
Section: Discussionmentioning
confidence: 99%